Evaluation and Management of Delirium - Ryan, Sophia L.; Kimchi, Eyal Y. (Seminars in Neurology, 2021)
Delirium, sometimes referred to as encephalopathy, is an acute confusional state that is both common in hospitalized patients and associated with poor outcomes. For patients, families, and caregivers, delirium can be a traumatic experience. While delirium is one of the most common diagnoses encountered by the consulting neurologist, the majority of the time it will have been previously unrecognized as such by the care team. Neurologic syndromes such as dementia or aphasia can either be misdiagnosed as delirium or may coexist with it, necessitating careful neurologic assessment. Once the diagnosis of delirium has been established, a careful evaluation for predisposing and precipitating factors can help uncover modifiable contributors, which should be addressed as part of a multicomponent, primarily nonpharmacologic intervention. Importantly, delirium management, which begins with comprehensive prevention, should emphasize the humanity of the delirious patient and the challenges of caring for this vulnerable population. When considered, delirium represents an important opportunity for the neurologist to substantially enhance patient care.
Keywords: delirium; encephalopathy; consultation; agitation